STRATEGY OF IMPLEMENTATION OF THE CONCEPT OF THE NATIONAL PROGRAM OF MILITARY-PATRIOTIC EDUCATION «HORTING-PATRIOT» - Borodai, Eduard (International Journal of Innovative Technologies in Social Science, 2020)
The urgency of the proposed Concept of the national program of military-patriotic education of children and students of Ukraine is due to: the need of the Armed Forces of Ukraine and other military formations to call up for military service citizens with a high level of moral, psychological and physical development; the lack in the state of an effective system of training citizens for military service and defense of the Fatherland, which can in a short time to restructure their activities in accordance with the requirements of the time; lack of a single scientific and methodological center for curriculum development, methods of preparing young people for military service, criteria for assessing military-patriotic education, lack of necessary educational facilities in secondary schools for pre-service training and military-patriotic education: low level of training for secondary schools in the subject «Defense of the Fatherland», which does not fully ensure the quality of teaching this subject. The purpose of the Concept is to create centers for military and patriotic education of children and students in all regions of Ukraine within the national system of training citizens for military service and defense of the Fatherland.